Effect of starter diet supplementation on rumen epithelial morphology and expression of genes involved in cell proliferation and metabolism in pre-weaned lambs. (26th February 2018) - Sun, D. M.; Mao, S.Y.; Zhu, W.Y.; Liu, J.H.
Abstract : Starter feeding is usually used in lamb production to improve rumen development and to facilitate the weaning process, but molecular mechanism of which is not well understood. Therefore, the objective of this study is to investigate the effect of starter feeding on the expression of ruminal epithelial genes involved in cell proliferation, apoptosis and metabolism in pre-weaned lambs. We selected eight pairs of 10-day-old lamb twins. One twin was fed ewe milk (M, n =8), while the other was fed ewe milk plus starter (M+S, n =8). The lambs were sacrificed at 56 days age. Results showed that the lambs fed M+S had lower pH in the rumen and a higher concentration of acetate, propionate, butyrate and total volatile fatty acid (VFA). Compared with the M group, the concentration of β -hydroxybutyric acid in plasma had an increased trend, and the concentration of IGF-1 in plasma had an decreased trend in the M+S group. The length, width and surface of rumen papillae increased in the M+S group compared with the M group; this was associated with increased cell layers in the stratum corneum, stratum granulosum and total epithelia. Messenger RNA (mRNA) expression of proliferative genes of cyclin A, cyclin D1 and cyclin-dependent kinase 2 in the ruminal epithelia of M+S lambs was increased compared with M only lambs. The mRNA expression of apoptosis genes of caspase-3, caspase-8, B-cell lymphoma-2 (Bcl-2) and Bcl-2-associated X protein (Bax) in the M+S group was decreased compared with M group, but the ratio of Bcl-2 to Bax were not changed between the two groups. Expression of IGF-1 mRNA was decreased, but the mRNA expression of IGF-1 receptor was higher in ruminal epithelia in the M+S group. Furthermore, the mRNA expression of VFA absorption and metabolism genes of β -hydroxybutyrate dehydrogenase isoforms 1 and 3-hydroxy-3-methylglutaryl-CoA lyase had an increased trend in the M+S group than in the M group, but the mRNA expression of 3-hydroxy-3-methylglutaryl-CoA synthase isoform 1, monocarboxylate transporter isoform 1 and putative anion transporter isoform 1 had a decreased trend in the M+S group than in the M group. These results suggest that starter feeding increased proliferation and inhibited apoptosis of ruminal epithelial cells, and may promote the VFA metabolism in ruminal epithelium in pre-weaned lambs. These findings provide new insights into improving rumen development by nutritional intervention strategies in pre-weaned lambs.